2013
DOI: 10.1017/s1751731112001103
|View full text |Cite
|
Sign up to set email alerts
|

Expression of leptin and its receptor genes in the ovarian follicles of cycling and early pregnant pigs

Abstract: Leptin is a polypeptide hormone produced primarily by adipocytes. It has been implicated in the regulation of satiety and energy homeostasis. Leptin has been suggested to play a role in reproduction based on its involvement in the regulation of the hypothalamic-pituitary-gonadal axis via endocrine, paracrine and/or autocrine pathways. The aim of the present study was to localize the cellular distribution of leptin and the long isoform of leptin receptor (OB-Rb) genes in porcine ovarian antral follicles and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
1
10
1
5
Order By: Relevance
“…Similar to vertebrate LEPR s in fish (72), chicken (73), pig (74), cow (75), rat (76), and human (77), the Dome protein of Drosophila is critical for germline and follicle cell development through UPD signaling (78). Recent reports of a putative leptin signaling system in D. melanogaster through the UPD2 and Dome proteins (71), which are associated with phenotypes from tissue development (79), memory (80), and reproductive systems (78), proposes conserved leptin signaling components in invertebrates.…”
Section: Evolution Of Leptin Signaling: Invertebrate Leptin Signalingmentioning
confidence: 99%
“…Similar to vertebrate LEPR s in fish (72), chicken (73), pig (74), cow (75), rat (76), and human (77), the Dome protein of Drosophila is critical for germline and follicle cell development through UPD signaling (78). Recent reports of a putative leptin signaling system in D. melanogaster through the UPD2 and Dome proteins (71), which are associated with phenotypes from tissue development (79), memory (80), and reproductive systems (78), proposes conserved leptin signaling components in invertebrates.…”
Section: Evolution Of Leptin Signaling: Invertebrate Leptin Signalingmentioning
confidence: 99%
“…For example, progesterone (P4) is a steroid hormone produced by ovarian cells, which is involved in control of ovarian functions, embryonic development and in mammary gland functions (Hagan, Faivre, & Lange, 2009;Sirotkin, 2014). Peptide hormone leptin (L) is a product of adipose and some other tissues (including porcine ovarian cells, Smolinska, Kaminski, Siawrys, & Przala, 2013), which mediates the effects of nutrition and metabolism on reproduction at both hypothalamohypophyseal and ovarian levels (Sirotkin, 2014). L can activate the secretion of hypothalamic luteinizing hormone-releasing hormone (LH-RH) and hypophysial gonadotropins (Garcia-Diaz, Campion, Milagro, & Martinez, 2007;Smith et al, 2006), affect secretion of P4, androgens and oestradiol by cultured rat, bovine, porcine and human ovarian cells (Ricci, Yorio, & Faletti, 2006).…”
mentioning
confidence: 99%
“…A number of studies found that the leptin receptor is expressed in the porcine granulosa and theca cells, as well as the corpus luteum and ovarian stroma (Lin et al., ; Ruiz‐Cortes et al., ; Smolinska et al., ). Both leptin and its receptor have been identified in human (Loffler et al., ), murine (Ryan et al., ) and pig (Smolinska et al., ) ovarian tissues and related to steroidogenesis (Spicer and Francisco, ). Stimulatory effect of leptin on human steroid production and aromatase activity has been described (Karlsson et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have found that leptin inhibits steroid production in various species (Barkan et al., ; Caprio et al., ). In pig, the expression of leptin was demonstrated only in the antral follicles during the follicular phase and in luteal phase (Smolinska et al., ). To our knowledge, differences in leptin expression in the porcine ovary in different reproductive stages have not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%